The Properties of Nanostructured ZnO Thin Film via SolGel Coating - Suwanboon, Sumetha (Asian Health, Science and Technology Reports, 2008)
This review presents the recent studies on improving the structural, electrical, and optical properties of nanocrystalline ZnO thin film prepared from solgel coating for possible applications to photoconductor, UV optoelectronic, integrated sensor, and transparent conducting oxide electrodes. ZnO thin films can be grown on an inexpensive substrate such as glass at relatively low temperature and these films might have many advantages over indium doped SnO2 and GaN thin films.